Reappraisal of profibrotic phenotype and cell-cycle state of renal tubular epithelium after ischemia–reperfusion injury - Daichi Fukaya; Wakako Kosakai; Tetsuya Sato; Tsutomu Inoue; Hiroaki Amano; Takeru Kusano; Hirokazu Okada (PLoS ONE, 2026)
Chronic kidney disease progression involves phenotypic changes in tubular epithelial cells, and recent studies have highlighted the relationship between such pro-fibrotic phenotypes and cell cycle arrest in injured tubular epithelial cells undergoing repair. We investigated these processes using a mouse unilateral ischemia–reperfusion injury model with γGT.Fucci2aR mice, which express fluorescent cell cycle markers, and in vitro experiments with human kidney-2 cells and public single-cell RNA sequencing data. In the unilateral ischemia–reperfusion injury model, mVenus-positive cells (S/G2/M phases) in the γGT.Fucci2aR mice peaked on Day 3 post-injury, then rapidly declined. In kidneys with progressive tubular atrophy and interstitial fibrosis between 7–12 days post-injury, S/G2/M phase cells were limited. These findings were corroborated by analysis using public single-cell RNA sequencing data from the same mouse models, which confirmed dynamic cell cycle changes in the acute phase post-injury but no significant G2/M phase cells in the chronic phase. In vitro experiments with human kidney-2 cells demonstrated that cellular communication network factor 2 and transforming growth factor-β expression increased significantly as proliferating cells reached confluence and cell cycle progression slowed. Pro-fibrotic phenotypes in tubular epithelial cells were not exclusively acquired by G2/M-arrested cells, as reported in previous studies, but can also be acquired by cells in the quiescent G0/G1 phase during normal cell cycling. To develop novel therapeutics for chronic kidney disease, regulating pro-fibrotic gene expression in injured tubular epithelial cells, independent of specific cell cycle phases, appears to be crucial.